Exile literature, 1933-1945. - Brandt, Willy 1913-1992 (Inter Nationes, 1968)
Addresses delivered by Willy Brandt and others on the occasion of a meeting held Jan. 17-19, 1968 in Luxemburg by writers, scientists, and politicians who had been in exile, 1933-1945.